2017
DOI: 10.5812/ccn.12453
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nutrition Education Program on Biochemical Parameters Among Patients With Chronic Kidney Disease Undergoing Hemodialysis

Abstract: Background: Nutrition is considered an important part of treatment in patients with chronic kidney disease (CKD). Therefore, poor nutrition leads to decreased life quality and increased complications of hemodialysis as well as mortality in these patients. This study aimed at investigating the effect of nutrition education program (NEP) on biochemical parameters among patients undergoing hemodialysis. Methods: This quasi-experimental study was conducted on 30 patients who referred to hemodialysis unit at Ayatol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…In line with the current guidelines, our findings agreed that the NE program provides supporting management to delay CKD progression. Similarly, the previous studies demonstrated that face-to-face NE was associated with decreases in BUN [34,35] and serum creatinine levels [35,36] in hemodialysis patients.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In line with the current guidelines, our findings agreed that the NE program provides supporting management to delay CKD progression. Similarly, the previous studies demonstrated that face-to-face NE was associated with decreases in BUN [34,35] and serum creatinine levels [35,36] in hemodialysis patients.…”
Section: Discussionsupporting
confidence: 63%
“…Additionally, hemodialysis patients receiving face-to-face NE for 3 months significantly decreased serum creatinine, potassium, and phosphorus levels compared to the control group receiving routine education rather than NE [36]. Similarly, hemodialysis patients significantly reduced serum sodium, potassium, and calcium levels after receiving four 30-min face-to-face NE sessions weekly for 30 days as compared to the baseline before NE intervention [34]. The intervention of NE has been proposed to improve the health outcomes and self-care skills of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that performed educational interventions, it is stated that education is effective on the adherence to treatment of hemodialysis patients, and it provides behavioral changes in patients. [21][22][23][24] Self-management interventions are complex behavioral strategies and these interventions provide monitor and regulation of behavior and reinforcement. 25 The core elements of self-management interventions consist of self-observation of the targeted behavior, self-recording, and providing reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…Education can be given to patients by healthcare professionals. Studies that performed educational interventions, it is stated that education is effective on the adherence to treatment of hemodialysis patients, and it provides behavioral changes in patients 21‐24 …”
Section: Introductionmentioning
confidence: 99%